Clinical Characteristics and Survival of Patients with Malignant Ovarian Tumors in Addis Ababa, Ethiopia - Piszczan, Swantje (Oncologist, 2019)
BACKGROUND. Ovarian cancer is the third leading cause of cancer death among women in Ethiopia, with about 2,550 diagnosed cases and 2,000 deaths each year. The incidence and mortality rates of this disease have been increasing in Ethiopia and other parts of sub‐Saharan Africa over the past decades because of changing lifestyle and reproductive factors. In this study, we describe the clinical characteristics, treatment patterns, and survival of patients with ovarian cancer in Ethiopia. MATERIALS AND METHODS. This retrospective cohort study included 485 patients diagnosed between January 2009 and October 2015 at Addis Ababa University Hospital, Zewditu Memorial Hospital, or registered in the Addis Ababa population‐based cancer registry. Follow‐up data were obtained via telephone. Primary endpoint was all‐cause mortality. RESULTS. The median age was 46 years (range, 11–95). The estimated 1‐ and 2‐year overall survival rates were 78% (95% confidence interval [CI] 0.741–0.82.5) and 59% (95% CI, 0.538–0.646), respectively. Of those patients with result available (n = 423), 73.0% had epithelial cancers. Almost half were classified as Federation of Gynecology and Oncology stage III or IV (48.2%; stage available n = 201) resulting in worse outcomes (hazard ratio [HR], 2.91 [CI 0.67–12.64] and 3.03 [0.69–15.79], respectively). Four out of five patients received some form of surgery (82%), three out of five received platinum‐containing chemotherapy. Patients with residual tumor after surgery (n = 83) showed worse survival outcome (HR, 2.23; 95% CI 1.08–4.49). CONCLUSION. Our study revealed substantial treatment gaps with respect to surgery and adequate chemotherapy. Higher stage, residual tumor and lack of chemotherapy impaired the outcome. Access to higher standards of ovarian cancer treatment is urgently needed in Ethiopia. IMPLICATIONS FOR PRACTICE. Ovarian cancer is often a fatal disease in high resource settings; now it is also becoming important in Ethiopia. This study included 485 women with malignant ovarian tumors treated in Addis Ababa who had a mean age of only 46 years because of the young population structure. Three quarters had the typical epithelial cancer, with half presenting with advanced stage III and IV. Improved oncologic surgery and sufficient chemotherapy could possibly improve their outcome. The relatively high proportion of women with nonepithelial cancer need adequate treatment options to have good prognosis.